Poklicna identiteta slovenskih medicinskih sester - Škerbinek, Ana (Obzornik zdravstvene nege, 2000)
The article presents self image and professional identity of Slovenian nurses.The data have been gathered by means of an anonymous questionnaires applied to a chosen pattern of nurses and nursing technicians. Positive professional identity is extremely important because it is always linked to the way others see and judge us.
Keywords: Job description; Job satisfaction; medicinske sestre; Nurses; Nursing care; poklic; Questionnaires; samopodoba; Workplace; zdravstvena nega